KINERJA LEMBAGA PERWAKILAN RAKYAT DAERAH (Studi Deskriptif Kualitatif Di DPRD Kota Bengkulu) - Harius Eko saputra (UNIVED PRESS, Universitas Dehasen Bengkulu, 2014)
Almost every day, in various mass media, especially in newspapers, it is found that there are so many complaints and unsatisfactory opinions from the community, as the customer, towards the current implementation of public service. These complaints and unsatisfactory opinions can describe how bad the quality of the current public service is, which is benefited by the community. It may be the right time for the community to be treated as citizens, who will have rights and give priority to their rights for being served afterwards. They are not anymore being considered as clients who previously have no any choice in choosing and in determining what kind of service that they really want to. There are so many results from research, seminar and writings that are conducted by experts in which their works talk about the implementation of a good and qualified public service. Currently, however, the qualified public service has not yet implemented as should have been. The implementation of public service still acts as however it please to be and only emphasize on its own interest without considering the consumer’s importance as the party that should really be served as well as possible. For this reason, a research, which is done in Service Integrated Unit of the Jember Regency, tries to find out any factors affecting quality of the public services. The main core of the public service implementation is the quality of norm of the service executor. The matter that should be realized is that the executor is the person who should serve for the community, and the community is the one who should be served as well as possible.Keywords: Implementation of public service, legislatif